Hubungan Pola Makan dan Aktivitas Fisik dengan Status Gizi Remaja di Muhammadiyah Boarding School Yogyakarta - Oktavia, Rahayu; Wulandari, Pipit; Anggoro, Sarni (Universitas Widya Mataram, 2024)
The purpose of this study is to determine the correlation between diet and physical activity with the nutritional status of adolescents at Muhammadiyah Boarding School, Pleret, Bantul, Yogyakarta, in 2023. This study uses a type of quantitative research with data collection carried out in this study using a cross sectional design. The source of research data comes from primary data, namely observation, documentation, and filling out questionnaires. The total sample used was 78 students.The results of the Chi-Square test analysis on the correlation between diet and nutritional status of adolescents at Muhammadiyah Boarding School Pleret showed a significant value of 0.000, meaning the P value is 0.000 < 0.05. The results of the Chi-Square test for physical activity showed a significant value of 0.033, with a P value of 0.033 < 0.05. Thus, Ho is rejected, indicating a significant correlation between diet, physical activity, and nutritional status of adolescents at Muhammadiyah Boarding School Pleret in 2023.